THE IMPACT OF WAR ON DEMOCRATIC TRANSFORMATION IN DEVELOPING COUNTRIES - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The important of this topic is to find why government and the opposition parties are not reaching to last agreement to bring sustainable development to citizens of South Sudan, to determine the factors that distracted the lasting peace in the country, to investage why the leader are not agree to each other’s.The research design adapted in this study was survey in which the research went to the field to collect data directly. Sample size in this study was 50 respondents here the researcher employed simple random sampling techniques to select 100 respondents from population. Questionnaires and interviews were used to collect data. Data analysis was presented in tables with emphasis to frequencies and percentages. The study established that Ministry of Parliamentary Affairs play crucial role in South Sudan Development. The Ministry of Parliamentary Affairs is seek to improve the quality of life and effective participation development activities are results in mutual benefits and share responsibilities among the youth in the community.The study conclusion that for achieved of the goals set for the role of Ministry of Parliamentary Affairs should be ready to faced difference kind of risks and challenges that they may encounter during their work.